Evaluation of methionine and tryptophan derivatised vehicles: Met-ac-TE3A/Trp-ac-TE3A for tumor imaging1. Issue 52 (10th June 2015) - Singh, Sweta; Tiwari, Anjani K.; Varshney, Raunak; Mathur, Rashi; Hazari, Puja P.; Singh, B.; Mishra, Anil K.
<x xml:space="preserve">Abstract</x> Two novel amino acid (methionine and tryptophan) appended 1, 4, 8, 11-tetraazacyclotetradecane triacetate (TE3A) compounds Met-ac-TE3A and Trp-ac-TE3A were synthesized and evaluated for imaging applications.